2018
DOI: 10.1002/bsl.2332
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality applications for diagnosis, risk assessment and therapy of child abusers

Abstract: Despite the successful application of virtual reality (VR) in a wide variety of mental disorders and the obvious potentials that VR provides, the use of VR in the context of criminology and forensic psychology is sparse. For forensic mental health professionals, VR provides some advantages that outrun general advantages of VR, e.g., ecological validity and controllability of social situations. Most important seems to be the unique possibility to expose offenders and to train coping skills in virtual situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
1
18
0
5
Order By: Relevance
“…In other VR programs, however, a high degree of attention has been paid to digitally individualizing the stimuli in a replicable way. For example, in the VR intervention described by Fromberger et al (28), virtual child characters were selected based on the sexual offender's level of attraction to them and a digital supermarket with a plethora of groceries were painstakingly constructed. Despite this, the actual choices of interactions/behaviors available to the offender within the intervention appear to be limited to approaching or not approaching the virtual child character.…”
Section: Discussionmentioning
confidence: 99%
“…In other VR programs, however, a high degree of attention has been paid to digitally individualizing the stimuli in a replicable way. For example, in the VR intervention described by Fromberger et al (28), virtual child characters were selected based on the sexual offender's level of attraction to them and a digital supermarket with a plethora of groceries were painstakingly constructed. Despite this, the actual choices of interactions/behaviors available to the offender within the intervention appear to be limited to approaching or not approaching the virtual child character.…”
Section: Discussionmentioning
confidence: 99%
“…Though speculative, no one could dismiss the possibility that the use of sexbots in the treatment of sex offenders might have similar effects to the ones elicited by virtual reality, or viewing time, or virtual pornography. Research has demonstrated the potential of these techniques in the diagnosis, risk-assessment and treatment of sexual deviance, especially for child molesters [134]. The advent of sexbots might encourage their use in an immersive visual stimuli scenario for inducing sexual arousal, and assessing it with penis plethysmography (PPG) [135].…”
Section: Scientific Responsibility For Future Sexbots Researchmentioning
confidence: 99%
“…A busca resgatou 1.496 artigos, mas por meio da leitura dos resumos e palavras-chave, somente em 14 trabalhos foi identificado algum debate entre avaliação psicológica e ética. Desses, seis discutem sobre as novas tecnologias para avaliação e intervenção em Psicologia (Duncan, Velasquez, & Nelson, 2014;Fromberger, Jordan, & Müller, 2018;Luxton, 2014;Luxton, Pruitt, & Osenbach, 2014;Mueller, & Piper, 2014;Prentice, & Dobson, 2014), dois sobre a importância de psicólogos serem treinados para realizar avaliação psicológica (Evans, & Finn, 2016;Ready, & Veague, 2014), um sobre candidatos a cirurgia bariátrica (Rouleau, Rash, & Mothersill, 2016), um sobre coleta de dados com a população idosa (Diniz, & Amado, 2014), um sobre avaliação em contextos multiculturais e com poucos recursos (Laher, & Cockcroft, 2017), um sobre a população surda (Boness, 2016), um sobre dificuldades da atuação do psicólogo (Hazboun, & Alchieri, 2014) e um sobre processos éticos julgados no CFP (Zaia, Oliveira, & Nakano, 2018).…”
Section: A Discussão Da éTica Na Avaliação Psicológica a Partir Dos Dunclassified